Global Experiences with Special Economic Zones : With a Focus on China and Africa - Zeng, Douglas Zhihua (World Bank, Washington, DC, 2015)
This paper is intended to provide a brief overview of the different SEZ experiences in China and Africa, the key lessons that Africa can learn from China, as well as the recent Chinese zones in Africa. For this purpose, the paper is structured in the following way: section 1 starts with definition of SEZs, then followed with the Chinese experiences (section 2), African experiences (section 3), the lessons that Africa can learn from China (section 4), Chinese zones in Africa (section 5), and then concludes.